2001
DOI: 10.1088/0031-9155/46/5/312
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of a model of tissue response to radiation based on the idea of functional subunits and binomial statistics

Abstract: This work investigates the existing biological models describing the response of tumours and normal tissues to radiation, with the purpose of developing a general biological model of the response of tissue to radiation. Two different types of normal tissue behaviour have been postulated with respect to its response to radiation, namely critical element and critical volume behaviour. Based on the idea that an organ is composed of functional subunits, models have been developed describing these behaviours. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…The normal tissue complication probability (NTCP) is used as a measure for the sensitivity of normal tissue for a given radiation treatment schedule. NTCP models are based on the damage probability of so called "functional subunits" (FSU) [8,18]. Of course, it is desirable to achieve a TCP close to 1, however, at the same time the NTCP must be at an acceptably low level.…”
Section: 34mentioning
confidence: 99%
“…The normal tissue complication probability (NTCP) is used as a measure for the sensitivity of normal tissue for a given radiation treatment schedule. NTCP models are based on the damage probability of so called "functional subunits" (FSU) [8,18]. Of course, it is desirable to achieve a TCP close to 1, however, at the same time the NTCP must be at an acceptably low level.…”
Section: 34mentioning
confidence: 99%
“…Other methods of reducing DVHs to a single dose or volume parameter have been proposed. The work of Cozzi et al (13) suggested that most current DVH reduction schemes are somewhat error‐prone because they can lead to DVH reductions inconsistent with the expected biological effect. The KB method was found to be one of the more robust of the available DVH reduction schemes.…”
Section: Methodsmentioning
confidence: 99%
“…The number of clonogenic cells can be determined using some of the following relations:) (43)(44)(45) (5) (6) where D 50 is the tumor dose required to obtain a TCP of 50%. In addition, an expression for TCP may be obtained if data of clonogenic cells are not available, in terms of sigmoidal dose response parameters as (43,44,46) (sigmoidal model for TCP):…”
Section: C2 Tcpmentioning
confidence: 99%
“…In addition, an expression for TCP may be obtained if data of clonogenic cells are not available, in terms of sigmoidal dose response parameters as (43,44,46) (sigmoidal model for TCP):…”
Section: C2 Tcpmentioning
confidence: 99%